Coloconger maculatus sp. nov., a species of short-tail eel from eastern Taiwan (Anguilliformes: Colocongridae) - Ho, Hsuan-Ching; Tang, Chi-Ngai; Chu, Tah-Wei (Zootaxa, 2021)
A new species of Coloconger is described from a large female collected off eastern Taiwan. It can be distinguished from congeners by having a large black blotch on rear portion of tail; posterior end of tail white; and combination of characters: head small 15.7% TL; 4 supratemporal pores, middle 2 in pair; 7 supraorbital pores, 2 pores over posterior nostril; 12 or 14 infraorbital pores; 14 preoperculomandibular pores; 226 dorsal-fin rays and 122 anal-fin rays; preanal vertebrae 77 and total vertebrae 145; rictus through a vertical of posterior margin of pupil; snout shorter than eye diameter; distance between origins of pectoral and dorsal fins 69.4% pectoral-fin length; and body brownish gray dorsally, light gray ventrally, and dorsal fin dark gray. Data and variations of Coloconger japonicus found in Taiwan are provided and discussed.